Exploring the therapeutic potential of phytochemicals apigenin and ellagic acid in managing polycystic ovarian syndrome and its comorbidities: a comprehensive review - Balkrishna, Acharya; Rana, Maneesha; Mishra, Shalini; Agrawal, Ritik; Rajput, Satyendra Kumar; Dhanasekaran, Muralikrishnan; Rana, Mamta; Arya, Vedpriya; Ramu, Ramith; Upadhayay, Ashutosh; Singh, Shalini (Frontiers in Endocrinology, 2025)
Polycystic Ovarian Syndrome (PCOS) is a complex endocrine and metabolic disorder affecting women of reproductive age, characterized by hyperandrogenism, insulin resistance, chronic inflammation, and ovulatory dysfunction. Conventional therapies, such as oral contraceptives, insulin sensitizers, and anti-androgens, primarily offer symptomatic relief and are often associated with chronic adverse effects, underscoring the need for safer and more holistic alternatives. Naturally occurring bioactives have emerged as promising adjunct or alternative therapeutic agents in this context. This review critically examines the therapeutic potential of two phytochemicals or natural bioactives, apigenin and ellagic acid, in the integrative management of PCOS and its associated metabolic disturbances and comorbidities. Apigenin, a flavonoid abundantly present in parsley, chamomile, and citrus fruits, and ellagic acid, a polyphenol found in pomegranates and berries, both demonstrate significant anti-inflammatory, antioxidant, insulin-sensitizing, and anti-androgenic activities. Mechanistic studies reveal their ability to regulate ovarian steroidogenesis, suppress pro-inflammatory cytokines, improve insulin sensitivity via the PI3K/Akt signaling pathway, and reduce hyperandrogenism by inhibiting 5α-reductase. Preclinical and preliminary clinical studies support the efficacy of these treatments in restoring ovarian morphology, normalizing hormonal profiles, and ameliorating metabolic dysfunctions in PCOS models. Although limited by poor bioavailability, both compounds exhibit favorable safety and metabolic profiles, and emerging formulation approaches such as nano-delivery systems, phytosomes, and liposomes offer promising strategies to enhance their clinical applicability. This review advocates incorporating apigenin and ellagic acid into integrative PCOS treatment strategies. It highlights the need for well-designed clinical trials to validate efficacy, establish standardized dosing, and develop advanced delivery systems.